Isolation, identification of pathogenic Acanthamoeba from drinking and recreational water sources in Saudi Arabia - Vijayakumar, Rajendran (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was conducted to isolate and identify the Acanthamoeba species from various water sources such as drinking water, tap water, swimming pool, and other recreational water. Materials and methods: During the study period, 57 water samples were collected from various sources such as tap water, drinking water, swimming pool, and recreational water. All samples were processed and cultured on non-nutrient agar medium (NNA) with Escherichia coli overlay for the isolation of Acanthamoeba species. Organism identified based on the microscopic morphology of cyst and trophozoites forms. The pathogenicity of Acanthamoeba was analyzed by thermotolerance and osmotolerance assays. Results: Acanthamoeba were detected in 10 out of 57 (17.5%) examined water samples. The high percentage of positivity was observed in bore well water stored in tanks (37.5%) and in recreational water samples (26.7%). All processed drinking water samples were free from Acanthamoeba. Based on pathogenicity test assays, four (40%) were pathogenic and three (30%) were non-pathogenic. The observed frequency of Acanthamoeba spp. was compared with available literature worldwide. Conclusion: This study is the first report showing the distribution of Acanthamoeba in various water sources in the central region of Saudi Arabia and confirms that the high percentage presence of pathogenic strains in recreational water could threat contact lens wearers. Further research works are required to identify the prevalence of pathogenic Acanthamoeba from various water sources in Saudi Arabia. http://doi.org/10.5455/javar.2018.e296